Intracerebral opportunistic infections caused by immunosuppressants after orthotopic liver transplantation: Report of two cases and literature review - Guo, Yafei; Zhu, Zebin; Cai, Wei; Tao, Shengwei; Yin, Dalong (Frontiers in Immunology, 2022)
Central nervous system (CNS) infections in adults are rare because of normal immunity and the existence of the blood brain barrier, which prevents the invasion of pathogenic microorganisms. Liver transplant recipients are at an increased risk of opportunistic infections (OI) due to immunosuppressive therapy compared to those with normal immunity. Early diagnosis and timely implementation of treatment are critical for the successful treatment of these infections. We present two cases of intracerebral OI after orthotopic liver transplantation (OLT), with different clinical presentations. Patient 1 presented with epileptic seizures, mainly manifested as unresponsiveness, unconsciousness, and coma complicated with involuntary limb twitching. Patient 2 presented with a consciousness disorder, mainly manifested as unclear consciousness content, poor orientation, calculation power, and logical ability. Next-generation sequencing (NGS) examination of the cerebrospinal fluid confirmed human herpesvirus 6 B (HHV-6B) infection in patient 1 and intracranial Aspergillus infection in patient 2. Intracranial OI has insidious onset and atypical clinical manifestations. NGS can allow for the proper diagnosis and monitoring of the effects of treatment.